Manejo técnico de la monilla “Moniliophthora roreri” en el cultivo de cacao (Theobroma cacao) en el recinto cuatro esquinas - Llanos Chica, Darlin Miguel (2019)
The research work was carried out in the four corner agricultural enclosure, belonging to the Montalvo Canton of the province of Los Ríos, with the aim of obtaining knowledge about the main disease that occurs in the cultivation of cocoa that is sown and produced in this agricultural area of the province and identify what are the main agricultural factors that are influencing the development of this disease, identify what are the controls that are performed for it. Within the general methods that were applied to the study, the deductive and inductive methods were used for this investigation, due to the hypothesis that was raised and verified throughout the development of the research in order to reach the conclusions and recommendations of the work . In the evaluation carried out in the four-corner enclosure, it was known that the number of plantations affected by cocoa cultivation due to this disease are many among which the following agricultural activities were identified that are not carried out properly such as: adequate phytosanitary pruning, Clearing, proper fertilization, drainage among others. For which technical measures are carried out to be able to control them by performing all phytosanitary practices from the evaluation in the field by the owners along with their specialized technicians, whether they are from the Ministry of Agriculture or private companies.